Towards object-based image editing - Zhou, Hailing (2012)
With the increasing use of images in web design, document processing, entertainment, medical analysis, virtual environment creation, etc., the demand is dramatically growing for effective editing techniques that can fast and accurately create, compose, render and manipulate image contents. In recent years, plenty of research has been conducted for these tasks. However, the current techniques for these tasks are still far away from being satisfactory. It usually needs extensive user guidance, with painstaking time and effort, to produce a desired result. Our research thus investigates new techniques and tools for effective creation, extraction, composition, and other manipulations of image contents.